2019
DOI: 10.1155/2019/8073057
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Predictors of Obesity and Overweight among Adults Visiting Primary Care Settings in the Southwestern Region, Saudi Arabia

Abstract: Introduction. Obesity is becoming the most common health problem of the 21st century, as it will contribute significantly to the high prevalence of cardiovascular disease in developing countries. The main objective of our study was to estimate the prevalence of obesity and overweight among adults attending primary health care settings, southwestern region of the Kingdom of Saudi Arabia. Methods. The studied population was composed of adults visiting primary health care centres in the southwestern region of Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 27 publications
3
28
1
Order By: Relevance
“…Men were more overweight than women, while women were more obese than men. This nding is consistent with a recent report in Kuwait [9] and earlier reports in other countries in the GCC such as Qatar [21], Saudi Arabia [22,23], United Arab Emirates [24] and Bahrain [25]. Earlier cultural practices whereby women were discouraged from engaging in voluntary exercise, and valued for plumpness may, in combination with increasing consumption of calorie dense western foods, be a contributing factor to higher prevalence of obesity in women compared to men [26][27][28] The trend to greater levels of overweight and obesity with advancing age has been studied extensively [29][30][31] and is evident also in our results.…”
Section: Discussionsupporting
confidence: 93%
“…Men were more overweight than women, while women were more obese than men. This nding is consistent with a recent report in Kuwait [9] and earlier reports in other countries in the GCC such as Qatar [21], Saudi Arabia [22,23], United Arab Emirates [24] and Bahrain [25]. Earlier cultural practices whereby women were discouraged from engaging in voluntary exercise, and valued for plumpness may, in combination with increasing consumption of calorie dense western foods, be a contributing factor to higher prevalence of obesity in women compared to men [26][27][28] The trend to greater levels of overweight and obesity with advancing age has been studied extensively [29][30][31] and is evident also in our results.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings that females have a higher BMI than males across various income quintiles are in close contrast to other studies from the KSA [30] and the USA [60] that found higher BMI in men than in women. However, Al-Qahtani [30] explained that multiple pregnancies can be considered as one of the specific risk factors for increased food intake, coupled with cultural beliefs that women should not practice any form of physical activity until 40 days after delivery, thus leading to weight gain and evidently increasing BMI in women as compared to that in men.…”
Section: Discussioncontrasting
confidence: 75%
“…Aspects such as excessive drinking of soda and eating red meat were found to be associated with higher BMI [32][33][34][35]. In another study, Al-Qahtani [30] demonstrated that men have higher BMI than women, and that, across various income quintiles, the risks of being overweight or obese increase with an increase from low-to high-income quintiles. Although the situation is identical, the above-mentioned studies differ from our study in terms of both methods and focus.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the article titled “Prevalence and Predictors of Obesity and Overweight among Adults Visiting Primary Care Settings in the Southwestern Region, Saudi Arabia” [ 1 ], information was omitted from Acknowledgments in error. Acknowledgments is shown below.…”
mentioning
confidence: 99%